PENGARUH KOMPETENSI APARATUR DANA DESA, KOMITMEN ORGANISASI PEMERINTAH DESA, DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS DANA DESA - Aldian Prestya; David Adechandra Ashedica Pesudo (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this study was to examine the effect of apparatus, village government organizational commitment, and community participation on village fund accountability. This study uses mixed methods by combining two forms of research approaches, namely quantitative and qualitative. The population is village officials and village communities in Truko Village, Bringin District, Semarang Regency. The sampling technique used the slovin formula by distributing 24 questionnaire questions to 50 village communities and conducting interviews with the Village Head, Village Treasurer, and PLT Desa as village apparatus representatives to support statistical findings. This study uses primary data obtained by distributing questionnaires through direct surveys. Hypothesis testing using multiple linear regression analysis with SPSS application. The results showed that the competence of the village fund apparatus, village government organizational commitment, and community participation had a positive and significant effect on fund accountability.